2006
DOI: 10.1111/j.1365-2265.2006.02716.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum fetuin‐A with carotid arterial stiffness

Abstract: Serum fetuin-A level is associated with carotid arterial stiffness, independent of known atherogenic factors in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 30 publications
2
57
0
3
Order By: Relevance
“…A dual function of fetuin-A has been also suggested by Mori et al who found that the existence of kidney dysfunction may affect the different results in various studies 47 . Lower fetuin-A concentrations are associated with CVD events and mortality in ESRD subjects and high levels of fetuin-A are connected to atherosclerosis and CVD in non-renal patients 44 .…”
Section: Fetuin-a As a Marker Of Cardiovascular Diseasementioning
confidence: 91%
See 1 more Smart Citation
“…A dual function of fetuin-A has been also suggested by Mori et al who found that the existence of kidney dysfunction may affect the different results in various studies 47 . Lower fetuin-A concentrations are associated with CVD events and mortality in ESRD subjects and high levels of fetuin-A are connected to atherosclerosis and CVD in non-renal patients 44 .…”
Section: Fetuin-a As a Marker Of Cardiovascular Diseasementioning
confidence: 91%
“…Similarly, Vörös et al observed that individuals with previous myocardial infarction had significantly higher concentrations of fetuin-A than healthy controls 12 . Furthermore, a positive correlations of fetuin-A with arterial stiffness and increased intima-media thickness have been observed in healthy subjects and in patients with normal renal function 12,18,47 . Both the MetS and type 2 diabetes increase the risk of CVD (ref.…”
Section: Fetuin-a As a Marker Of Cardiovascular Diseasementioning
confidence: 98%
“…8 Serum fetuin has also been positively associated with carotid arterial stiffness, independent of known atherogenic factors in healthy subjects. 9 Therefore, fetuin's relationships with tissue calcification and atherogenesis are divergent, which reflects its diverse actions.…”
Section: Article P 2533mentioning
confidence: 99%
“…A fetuin-A-szint az érfali stiffnesszel, endotheldiszfunkcióval és az intima-media vastagsággal is pozitívan korrelált [29,30,31,32].…”
Section: A Fetuin-a öSszefüggése a Cardiovascularis Betegségek Markerunclassified